Effect of pioglitazone on plasma ceramides in adults with metabolic syndrome - Warshauer, Jeremy T.; Lopez, Ximena; Gordillo, Ruth; Hicks, Jessica; Holland, William L.; Anuwe, Estelle; Blankfard, Martin B.; Scherer, Philipp E.; Lingvay, Ildiko (Diabetes/metabolism research and reviews, 2015)
Background Metabolic syndrome (MetS) appears closely linked with ceramide accumulation, inducing insulin resistance and toxicity to multiple cell types. Animal studies demonstrate that thiazolidinediones (TZDs) reduce ceramide concentrations in plasma and skeletal muscle and support lowering of ceramide levels as a potential mediator of TZDs' mechanism of action in reducing insulin resistance; however, studies in humans have yet to be reported. This study investigated the effects of pioglitazone therapy on plasma ceramides to understand the mechanism by which TZDs improve insulin resistance in MetS. Methods Thirty‐seven subjects with MetS were studied in a single‐centre, randomized, double‐blind, placebo‐controlled trial comparing pioglitazone to placebo. Data were collected at baseline and after 6 months of therapy. The primary endpoint was the change from baseline in plasma ceramide concentrations. Results Treatment with pioglitazone for 6 months, compared with placebo, significantly reduced multiple plasma ceramide concentrations: C18:0 (p = 0.001), C20:0 (p = 0.0004), C24 : 1 (p = 0.009), dihydroceramide C18 :0 (p = 0.005), dihydroceramide C24:1 (p = 0.004), lactosylceramide C16:0 (p = 0.02) and the hexosylceramides C16:0 (p = 0.0003), C18 : 0 (p = 0.00001), C22:0 (p = 0.00002) and C24:1 (p = 0.0006). Additionally, significant reductions were found when ceramides were grouped by species: ceramides (p = 0.03), dihydroceramides (p = 0.02), hexosylceramides (p = 0.00001) and lactosylceramides (p = 0.02). The total of all measured ceramides was also significantly reduced (p = 0.001). Following treatment with pioglitazone, the decrease in some ceramide species correlated negatively with the change in insulin sensitivity (dihydroceramide C16:0, r = −0.54; p = 0.02) and positively with total (lactosylceramide C24:0, r = 0.53; p = 0.02) and high molecular weight (lactosylceramide C24:0, r = 0.48; p = 0.05) adiponectin measurements; however, significant associations with changes in liver fat and glycemic control reduction were not found. Conclusions Pioglitazone in individuals with MetS induces a potent decrease in plasma ceramides, and some of the changes correlate with changes in insulin resistance and adiponectin levels. Copyright © 2015 John Wiley & Sons, Ltd.